THE ROLE OF METONYMY IN ENGLISH NOVELS - Rakhmonova Amira Ulfatovna; Elise Brittain (Journal of new century innovations, 2023)
Abstract. The article is devoted to the stylistic study of metonymy, its types and role in novels. Moreover, a set of examples were analyzed.